Branded by law: Looking at India's Denotified Tribes - Dilip Dsouza; DSOUZA (Dilip) (New Delhi: Penguin Books, 2001)
This book is the result of the author's travels to meet with and talk to India's once-criminal - now denotified - tribes all over the country. Dilip D'Souza examines the lives of these people and explores what it means to brand entire communities criminal, to live your life treated as a criminal simply because you are born in that community. The book also traces the historical and political reasons certain tribes were notified 'criminal' by the British, the constitutional attempts to denotify them after Independence and their current situation.
Keywords: Law-Tribes; Branded as Criminals Tribe; Police Administration Attitudes